Comparison of RIPASA and Alvarado scoring in the diagnosis of acute appendicitis and validation of RIPASA scoring - Sanjive, Jeevan G.; Ramaiah, Ravi H. (International Surgery Journal, 2019)
Background: Acute appendicitis is one of the most common surgical emergencies. A delay in performing an appendicectomy in order to improve the diagnostic accuracy increases the risk of appendicular perforation and sepsis. We prospectively compared and validated RIPASA to Alvarado scoring system when applied to an Indian population. Methods: This study included all the patients presented in General Surgery and The Emergency Department of Manipal Hospital, Bangalore diagnosed to have acute appendicitis from October 2014 to March 2016. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), diagnostic accuracy, predicted negative appendicectomy and receiver operating characteristic (ROC) curve of the RIPASA and Alvarado scoring system were derived using SPSS statistical software. Results: 75 patients were included in the study. Using the RIPASA scoring system, 97.1% of patients who actually had acute appendicitis were correctly diagnosed, compared to only 52.85% when using the Alvarado scoring system. The sensitivity and the specificity of the RIPASA scoring system is 97.14% and 60% respectively. The diagnostic accuracy of RIPASA scoring system is 94.67% and that of Alvarado scoring system is 52%. The results indicate that the RIPASA scoring system is a better diagnostic tool for the diagnosis of acute appendicitis (p<0.001). Conclusions: It is observed that the RIPASA scoring system has higher sensitivity and higher specificity compared to Alvarado scoring. It also has higher diagnostic accuracy and consequently, it has low negative appendicectomy rate. It can be concluded that the RIPASA scoring can be effectively conducted for the better evaluation of acute appendicitis.